Penerapan Sistem HACCP di Hotel T & Y: Pengaruh Cara Penanganan Produk Terhadap Kualitas Keamanan Pangan - Irmawati, Irmawati; Jumiono, Aji; Amalia, Lia (Jurnal Ilmiah Pangan Halal, 2025)
The Hazard Analysis and Critical Control Point (HACCP) Food Safety System has become an important foundation in ensuring food safety in various industrial sectors, including the hotel industry. The aim of this internship was to evaluate the level of compliance of the hotel industry with the implementation of the HACCP standards as an effort to prevent and control food safety risks. The analysis of documentation was carried out to identify the potential deviations and obstacles facing a hotel industry of achieving compliance with HACCP standards. The results showed that the compliance levels of HACCP standards at hotel T & Y still facing certain challenges. Factors influencing the compliance with the HACCP standards are the management commitment, resources, and consistency in system implementation. The findings of this internship provide better understanding on the hotel compliance with HACCP standards to improve the implementation of the food safety systems. The compliance of HACCP standards was analyzed to contribute to the basis of the food safety practices for stakeholders and industry players of hospitality sector leading to increased food safety implementation in the future.